Tropical acacias planted in Asia: an overview - Turnbull, J.W.; Midgley, S. J.; Cossalter, C. (1998)
Australian acaias are planted in over 70 countries and cover about 2 million ha. This area is dominated by Acacia mearnsii, A saligna and A. mangium. In the past five years there has been a massive increase in the area of A. mangium plantations in Indonesia for pulpwood, and modest increases in China, India, Malaysia and Vietnam. The area now totals 600 000 ha. Recent development of plantations of tropical acacias is related to the profitability of growing acacia plantations due to the decreasing availability and higher costs of wood from natural forests, the opportunity to increase productivity of degraded sites, and the suitability of fast-grown wood for paper and reconstituted boards. Furthermore, research in genetics and breeding has identified superior provenances, developed seed orchards, and cloned fast growing hybrids. Molecular biology techniques have enabled rapid characterisation of genotypes and the detection of genetic variation. Nutrition research has demonstrated the value of phosphorus fertilisation on most sites and the benefits of inoculation with selected rhizobia and mycorrhizas. Surveys have identified potentially damaging pathogens and insects. All these have contributed greatly to reducing costs and increasing the potential returns from acacia plantations. There is an increased market acceptance of tropical acacia wood but research on wood properties and development of new products is a priority. As the large area of first-rotation plantations is harvested there is an increasing priority to develop management options to ensure minimal decline in site productivity and plantation yield in successive rotations.